Assessment of awareness in mobile phone waste recycling program among consumers in Kuala Lumpur / Nur Syazwina Kamardzaman - Nur Syazwina, Kamardzaman (2019)
Technology become more advance nowadays and the advancement produce a large numbers of electronic devices. The lifespan of the device become shorter when the feature become more tech. Due to the advancement of the technology, a large number of electronic waste were produce. E-waste are also one of the pollution that can affected the environment beside air and water pollution. Each year, roughly about 400 million waste mobile phones were generated around the world and make it as one of the cause of e-waste pollution (Xu, Zhang, He, Li, & Huang, 2016). This research project is to make assessment regarding consumers’ awareness and willingness on recycling e-waste mobile phone and tablet. This project also to make some recommendation regarding policies or framework for consumer e-waste recycling for Malaysia. Results shows that most of the respondents (56.67%) have 1-2 units of unused mobile phone. Respondents keeping their unused mobile phone at home as spare mobile phones. Respondents claimed that they changing their old mobile phone because it not working anymore, but choose to keep at home as spare phone. This shows that respondents have personal attachment with their old mobile phone and it will take some time to separate from old mobile phone. Majority of respondents (67.33%) stated that they never heard about any information regarding e-waste recycling. Its shows that lack of information lead to low rate of e-waste recycling. Respondents are aware that e-waste cannot mix with ordinary garbage, but lack of awareness make respondents do not recycle their unused mobile phone. Respondent have basic knowledge about materials inside mobile phone but less knowledge about mobile phone recycling. Information is important in enhancing consumers’ participation in recycling and government should provide more information about e-waste to increase consumers understanding especially about laws, regulation and recycling system. As respondents lack about e-waste recycling knowledge, their willingness to recycle their unused mobile phone are uncertain. The results shows that respondents are somewhat willing to take part if e-waste recycling was organised. This is due to their inadequate of information about the advantage when recycling waste mobile phone. Respondents need some incentive or compensation as motivation for their recycling action. Majority of respondents want cash payment or voucher as an incentive for their recycling action. Only 3.33% of respondents’ are willing to pay for recycling fee. Unwilling respondents (42.67%) stated that it is government responsibility to provide the recycling. Some also stated that it will burden their income and they are willing to sell the unused mobile phone to the second-hand market for low price. Experiences from developed countries shows that stable and complete recycling system require cooperation of all shareholder such as government, manufacturers, retailers, telecommunication service and consumers. Results shows that respondents thinks it is a responsibility of all share holder, and it shows they are aware about the cooperation of all shareholder. Improvement in law and regulation, development of e-waste infrastructural and education are some improvement that need to improve e-waste management system in Malaysia.